Generalized Exfoliative Dermatitis Suspected Caused by COVID-19 Vaccine : A Case Report - Hazlianda, Cut Putri; Dalimunthe, Dina Arwina; Astarina, Awalia (CoinReads Media Prima, 2023)
Introduction: Exfoliative dermatitis (ED) is a skin disorder characterized by the presence of erythema and scaling of the skin involving more than 90% of the total body surface area. One of the main etiologic factor of ED is drug hypersensitivity reaction. Vaccine administration can result in allergic reactions. The aim of this case report is to provide information on one of the forms of allergy to the COVID-19 vaccine, which can be ED. Case: A woman, 61 years old, with complaints of reddish patches accompanied by thickened scales and spread throughout the body accompanied by itching, pain in the skin, experiencing fatigue and chills since 3 days ago before the patient said she had received COVID-19 booster vaccine. The patient was diagnosed with generalised exfoliative dermatitis suspected to be caused by the COVID-19 vaccine. The patient was given therapy with oral methylprednisolone 36 mg/day with tapering if there was improvement, and topical urea 10% cream and hydrocortisone 2.5 % cream (face) and desoxymethasone 0.25 % cream (body). Discussion: ED is more common in men than women, with the highest incidence at the age of 40-60 years. The underlying therapy of ED is to address the aetiology and potential complications. The therapy was corticosteroids at a dose of 1-2 mg/kg/day with tapering, emollients and topical corticosteroids. The patient was given these therapies, showed clinical improvement within 5 weeks of treatment and no side effects. Conclusion: Exfoliative dermatitis can be idiopathic or secondary to drug hypersensitivity including vaccine administration. A complete history including history of drug administration and a thorough physical examination are required so that treatment can be given appropriately.